Advanced liquid chromatography/mass spectrometry profiling of anthocyanins in relation to set of red wine varieties certified in Czech Republic - Papoušková, Barbora; Bednář, Petr; Hron, Karel; Stávek, Jan; Balík, Josef; Myjavcová, Renáta; Barták, Petr; Tománková, Eva; Lemr, Karel (Journal of chromatography. A, Including electrophoresis and other separation methods, 2011)
Hyphenation of micro-liquid and ultra-performance liquid chromatography with a hybrid (QqTOF) tandem mass spectrometry was studied from the viewpoint of their applicability for monitoring of anthocyanin dyes in various cultivars and different vintages of red wine. After appropriate optimization both techniques proved to be suitable for this task. UHPLC system provided lower LOD and LOQ values as well as higher productivity and precision of retention parameters and peak areas with respect to micro-LC method. On the other hand, micro-LC method offers significant savings of mobile phase, less contamination of ion source of mass spectrometer and makes the nebulization process in electrospray much easier. In combination with principal component analysis (PCA), the method allows to elucidate long-term relations in a complete set of certified red wine cultivars grown in South Moravia (certified in Czech Republic until year 2005). Among the studied varieties Rubinet exhibit a specific anthocyanin profile. Especially interesting is a high content of 3-coumaroylglucoside-5-glucosides of malvidin and peonidin. Those dyes can be used as markers of artificial color enhancement. Principal component analysis applied to data processed with regard to enzymatic activity markedly facilitate classification among varieties. This approach allows resolution of teinturiers, variety Blaufränkish and partial classification of other varieties.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; vysokoúčinná kapalinová chromatografie; Česká republika; Anthocyanins; Wine; analýza hlavních komponent; Chromatography, High Pressure Liquid; Vitis; anthokyaniny; Czech Republic; víno; Principal Component Analysis